Variation of Sea Level on the Egyptian Mediterranean and Red Sea Coasts - Sharaf el Din, S. H. (The International Hydrographic Review, 2015)
Records for an 11-year period (1956–1966) from tide gauges at Alexandria and Port Said (Mediterranean), and Port Teufik (Red Sea) have been analysed and the relation between the mean monthly sea level and the meteorological factors examined. The seasonal and annual variations of sea level at these three ports were studied. At Alexandria and Port Said significant coherence was found between the monthly mean sea level and the atmospheric pressure. At Port Teufik the fluctuation of sea level can be mainly attributed to the wind and current regimes. The nontidal pattern of water circulation in the Suez Canal is chiefly affected by the wind regime at the two ends of the canal.